Gênero e poder: Diva Nolf Nazário na luta pelo voto feminino - Silva, Lenina Vernucci da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
A intenção desta dissertação é trazer a história e a luta da sufragista batataense Diva Nolf Nazário, uma jovem acadêmica de Direito que, junto com outras mulheres organizadas na Federação Brasileira para o Progresso Feminino (FBPF) reivindicou o direito ao voto e, de maneira mais ampla, a inclusão da mulher no espaço público da política. Diva Nolf juntou documentos para tirar seu título de eleitora e participar das eleições presidenciáveis de 1922, mas este direito foi negado a ela. A situação que passou a inspirou a publicar um livro em 1923 em que narra seu caso e traz um amplo levantamento sobre a temática do voto feminino. Pretende-se entender o indivíduo Diva Nolf enquanto sujeito singular e coletivo, pensar ela como única e plural, em suas relações com as demais militantes da FBPF. Para compreender a sua luta, foi realizada uma pesquisa de campo que envolveu o levantamento de documentos da FBPF; a análise de seu livro; de seu histórico escolar e uma entrevista com sua prima em Batatais que possibilitou reconstruir sua infância e sua família. A pesquisa bibliográfica trouxe como pano de fundo a formação da República brasileira e os anos 1920, analisados por meio do uso dos Estudos de Gênero e Feminismo e História das Mulheres

The main goal of the following paper is to bring to the lights the history of the suffragist fight of Diva Nolf Nazário. Diva was a young academic of law and- along with other women of the “Federação Brasileira para o Progresso Feminino” (FBPF) - she claimed to women the right to vote and, more widely, claimed the inclusion of women in the political space. Diva Nolf presented all the documents needed to have her permission to vote in the 1922’s general elections for president, but it was denied under the Constitution. The then law student did not agree with the decision and published in a newspaper an article that contested each argument of the judge who denied her permission to vote. Also in this article, Diva argued about the situation of women in Brazil. She claims, based upon her studies at the Largo do São Francisco College, that women are not considered nonvoters by the Brazilian Constitution and, thus, the denial of her permission to vote was against the Constitution. This situation inspired Diva to publish a book, in 1923, in which she brings the feminine vote to discussion. In order to understand her struggle, a field research, which handled carefully documents of the FBPF, was executed, an analysis of her book and of documents of the period she was a law student was done and her cousin from Batatais (Diva’s homeland) was interviewed. This made possible the understanding of her Family and childhood. The bibliographic research brought to this paper the formation of the Republic in Brazil and the 20’. Those elements were analyzed under the scope of Studies of Gender and Feminism and the History of Women. The analysis of Diva’s biography and her book helped understanding the process of struggle for the civil rights for women in the Republic and the role played by young women in achieving the women’s right to vote
Keywords: Nazario, Diva Nolf 1897-1966; Mulheres; Mulheres na politica; Voto; Republica